Treatment and clinical outcomes among stage II–IVA nasopharyngeal carcinoma patients with undetectable pretreatment Epstein-Barr viral DNA - Ci-ming Sun; Zhen Xu; Cheng-hao Li; Jun-xiang Chen; Xin-yi Su; Jing-xia Song; Shuang-hong Song; Qing-qing Xu; Yan-Ling Wu (Frontiers in Medicine, 2026)
Background This study analyzed the efficacy of multiple combined chemotherapy modalities on the long-term survival outcomes in stage II–IVA nasopharyngeal carcinoma (NPC) patients with undetectable pretreatment Epstein-Barr viral DNA (pre-DNA). Patients and methods We retrospectively analyzed 2,440 patients with stage II–IVA NPC with undetectable pre-DNA. Patients received any of the following treatment modalities: intensity-modulated radiotherapy (IMRT) alone; concurrent chemoradiotherapy (CCRT); induction chemotherapy (IC) + CCRT; IC + IMRT; or CCRT + adjuvant chemotherapy (AC) at Sun Yat-sen University Cancer Center between 2009 and 2015. Propensity score matching (PSM) was performed to balance variables. Matched patients in different treatment subgroups were analyzed by comparing survival outcomes. Results In the PSM cohorts, no significant differences were observed in disease-free survival (DFS), overall survival (OS), distant metastasis-free survival (DMFS), or locoregional relapse-free survival (LRRFS) between patients treated with IMRT combined with multiple chemotherapy modalities and those with IMRT alone (all P > 0.05). The estimated 5-year DFS, OS, DMFS, and LRRFS rates were 85.6% vs. 87.3% ( P = 0.33), 93.5% vs. 92.2% ( P = 0.64), 94.4% vs. 93.7% ( P = 0.96), and 92.0% vs. 94.0% ( P = 0.16), respectively. Similarly, no significant differences in 5-year DFS, OS, DMFS, or LRRFS were observed across subgroups receiving IMRT with or without concurrent chemotherapy (CC), IC followed by IMRT with or without CC, or CCRT with or without IC. However, among patients receiving CCRT with or without AC, the 5-year DFS (96.0% vs. 78.3%, P = 0.004), OS (98.0% vs. 88.1%, P = 0.027), and LRRFS (97.9% vs. 87.9%, P = 0.045) rates were significantly higher in patients without AC, whereas no significant difference was observed in DMFS (96.0% vs. 86.1%, P = 0.078). No significant differences in the survival outcomes of T3–4 stage and N2–3 disease were identified. Conclusions In patients with stage II–IVA NPC with undetectable pre-treatment EBV DNA, the addition of chemotherapy to IMRT was not associated with a statistically significant improvement in survival, regardless of whether they received induction, concurrent, or adjuvant chemotherapy. Further prospective validation is required.